2008
DOI: 10.1016/j.ydbio.2008.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Developmental control of sumoylation pathway proteins in mouse male germ cells

Abstract: Protein sumoylation regulates a variety of nuclear functions and has been postulated to be involved in meiotic chromosome dynamics as well as other processes of spermatogenesis. Here, the expression and distribution of sumoylation pathway genes and proteins were determined in mouse male germ cells, with a particular emphasis on prophase I of meiosis. Immunofluorescence microscopy revealed that SUMO1, SUMO2/3 and UBE2I (also known as UBC9) were localized to the XY body in pachytene and diplotene spermatocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
80
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(84 citation statements)
references
References 42 publications
4
80
0
Order By: Relevance
“…3E,F). Likewise, the number of BC7-positive primary spermatocytes (stages IX-XII) was greatly reduced and SUMO-1 positive XY bodies, which normally form during mid-pachynema (Koshimizu et al, 1995;La Salle et al, 2008), were absent from DMRT6 mutant testes (Fig. 3G,H).…”
Section: Dmrt6mentioning
confidence: 95%
“…3E,F). Likewise, the number of BC7-positive primary spermatocytes (stages IX-XII) was greatly reduced and SUMO-1 positive XY bodies, which normally form during mid-pachynema (Koshimizu et al, 1995;La Salle et al, 2008), were absent from DMRT6 mutant testes (Fig. 3G,H).…”
Section: Dmrt6mentioning
confidence: 95%
“…27,28 Further investigations revealed expression of sumoylation pathway genes and proteins, implying their functions in meiosis and spermiogenesis. 29 Although several reports refer to the SUMO pathway in oogenesis in Drosophila, [30][31][32] no direct evidence exists to link sumoylation to the meiotic cell cycle in Drosophila. A recent study on sumoylation in mouse oocyte development suggested that sumoylation may play a role in regulating gene expression by modulating transcription and RNA processing.…”
Section: Introductionmentioning
confidence: 99%
“…A similar localization of SUMO-2/3 in metaphase I spermatocytes was reported recently. 29 The most widely studied substrate of SUMO-2/3 is Topoisomerase II. Topoisomerase II is localized to and associates with the mitotic spindles and/or centromeres in several systems including budding yeast, 39 Xenopus egg extract 20,40 and human cells.…”
mentioning
confidence: 99%
“…The exact model of how SUMO regulates these functions is largely unknown. SUMO1 and SUMO2/3 have been recently studied during mouse and human spermatogenesis, where they were localized to different subdomains of germ and somatic testicular cells (Rogers et al 2004, Vigodner & Morris 2005, Vigodner et al 2006, Brown et al 2008, Metzler-Guillemain et al 2008, Vigodner 2009 expression patterns of genes related to the sumoylation pathway in different germ cell populations, but little is still known about the regulation of spermatogenesis by sumoylation (La Salle et al 2008). The localization pattern of SUMO1 and SUMO2/3 in the testis appeared not to be fully overlapping, although a recent study using SUMO1 knockout mice does not support differential roles of the SUMO isoforms during spermatogenesis .…”
Section: Introductionmentioning
confidence: 99%